(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the status of the financial income of selected bakery shops in terms of strategy or method, bread production demand, capital, and profit. The shortage was caused by traders allegedly hoarding supply to rake in profits and importing sugar from other countries not exceeding 150,000 metric tons (MT). From the results of this study, it is clear that the most common strategy used by business owners is adjusting ingredients used in baking, and bread production demand, capital, and profit have been greatly impacted by the crisis. Based on the results, business owners strongly agreed on cutting off the use of sugar in baking pastries; this led us to conclude that business owners would shift their products. Based on the results, respondents would increase their investments in capital due to the decrease in the supply of sugar and would base the salaries of their employees on the profit made by the shop. This study recommended that business owners should practically choose raw and processed ingredients they buy in groceries or markets, balance the ingredients they use in baking in order to maintain the richness of their products and remain able to satisfy the wants of their customers efficiently, and innovatively develop other products that can further help other business owners increase the success rate of their new product on the market. Lastly, we recommend business owners increase the visibility of their shops so that customers can easily buy their products and to increase public awareness.